Pemanfaatan Limbah Kotoran Rusa Timor (Rusa Timorensis) sebagai Pupuk Organik untuk Mendukung Pertanian Berkelanjutan: Studi Kasus Program RUFSA di Desa Cakura, Sulawesi Selatan - Andi Ade Ula Saswini; Muhammad Haris; Panji Triyanu Hermawan (The Journal General Health and Pharmaceutical Sciences Research, 2025)
The RUFSA Program (Rusa untuk Fertilizer Sustainable Agriculture) is an innovative initiative that transforms Timor deer (Rusa timorensis) manure waste from a conservation breeding site in Cakura Village, South Sulawesi, into organic biofertilizer. The program, implemented by PT Pertamina Patra Niaga Integrated Terminal Makassar in collaboration with the local community, aims to reduce manure waste, support wildlife conservation, and provide environmentally friendly fertilizer for sustainable agriculture. The method involves collecting deer manure directly inside the enclosure, mixing it with water and EM4 activator, and regularly stirring to ensure sufficient oxygen supply during a 7–14 day aerobic fermentation process. This approach not only reduces organic waste and minimizes unpleasant odor but also decreases the risk of disease transmission. The resulting biofertilizer is applied to cultivate odot grass (Pennisetum purpureum cv. Mott), small trees, and ornamental plants such as bougainvillea (Bougainvillea sp.), demonstrating practical benefits for local agriculture. Economically, the program contributes to an annual saving of IDR 3,240,000 by reducing the dependency on chemical fertilizers. Beyond its economic outcomes, RUFSA also strengthens community participation in environmental management and raises awareness of the importance of sustainable practices. Furthermore, the program aligns with the Sustainable Development Goals (SDGs), particularly those related to food security, economic growth, responsible consumption and production, and terrestrial ecosystem conservation. Overall, the RUFSA Program exemplifies an integrative approach that combines conservation, waste management, and community empowerment to promote environmentally responsible and sustainable agricultural development.